2014
DOI: 10.1007/s10346-014-0512-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rainfall threshold and its use in landslide hazard mapping of Kuala Lumpur metropolitan and surrounding areas

Abstract: This paper presents rainfall-induced landslide thresholds and predicts landslide hazard in Kuala Lumpur metropolitan city and surrounding areas. Landslide events from 2000 to 2012 were collected. The long and short antecedent rainfall days were prepared for landslide and non-landslide days simultaneously. First, threshold analysis was conducted by using data obtained from rainfall stations located in highly urbanized areas of Kuala Lumpur metropolis. Six rainfall gauges were selected, and the study area was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Thresholds are then constructed with lower rainfall demands to account for these landslides and because many other rainfall events that exceed the threshold do not trigger landslides, the predictive performance of the threshold is reduced. This may explain why in one of the zones in Kuala Lumpur, which was affected by several landslides with a major contribution from human activities despite being well protected against naturally occurring landslides, the predictive performance of its threshold was lower than the rest of the analyzed zones (Althuwaynee et al 2014). Third, many urban areas like Tegucigalpa are built upon active, slowly moving landslides or landslide deposits (Antronico et al 2013;Cascini et al 2005), given that these areas have more gentle slopes that are ideal for the development of unplanned infrastructure where flat, stable land is scarce (Cascini et al 2005).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Thresholds are then constructed with lower rainfall demands to account for these landslides and because many other rainfall events that exceed the threshold do not trigger landslides, the predictive performance of the threshold is reduced. This may explain why in one of the zones in Kuala Lumpur, which was affected by several landslides with a major contribution from human activities despite being well protected against naturally occurring landslides, the predictive performance of its threshold was lower than the rest of the analyzed zones (Althuwaynee et al 2014). Third, many urban areas like Tegucigalpa are built upon active, slowly moving landslides or landslide deposits (Antronico et al 2013;Cascini et al 2005), given that these areas have more gentle slopes that are ideal for the development of unplanned infrastructure where flat, stable land is scarce (Cascini et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Although the rainfall event immediately before a landslide is usually considered as the triggering rainfall, some research teams have found better results when the 3-day cumulative rainfall prior to the landslide is regarded as the triggering event (Althuwaynee et al 2014;Chleborad et al 2006;Zezêre et al 2015). Most researchers have considered convenient to evaluate different antecedent rainfall durations that usually range from 1 to 30 days.…”
Section: Considerations For the Construction Of Daily Versus Antecedementioning
confidence: 98%
See 2 more Smart Citations
“…In addition, some researchers have highlighted the importance of finding more robust hydrological bases to empirical rainfall thresholds for landslide initiation (Bogaard and Greco, 2018;Canli et al, 2017;Segoni et al, 2018). When data are scarce, a robust validation of a threshold model can be based on a quantitative comparison with alternate versions of the threshold (Althuwaynee et al, 2015) or with thresholds calculated with completely different approaches (Frattini et al, 2009;Lagomarsino et al, 2015). Wei et al (2017) investigated a rainfall threshold method for predicting the initiation of channelized debris flows in a small catchment, using field measurements of rainfall and runoff data.…”
Section: Introductionmentioning
confidence: 99%